Nutrition in the control and prevention of mental disorders: Serotonin precursor foods relieve anxiety (Research, Society and Development, 2025)
Anxiety is a natural behavior, but when prolonged, it can lead to problems such as mental disorders. It affects 9.3% of the Brazilian population and is influenced by poor eating habits. Processed foods rich in additives and toxins impair the absorption of nutrients, leading to behavioral imbalances caused by intestinal dysbiosis. On the other hand, a balanced diet, rich in vitamins and minerals, can improve the symptoms of mental disorders, even if it is not the main treatment. A lack of nutrients, such as tryptophan, can affect the production of serotonin, a neurotransmitter that is essential for regulating emotions. Some vitamins such as B and D, micronutrients such as magnesium, omega 3 and 6, and tryptophan are important for this process of serotonin production in the intestine. It is essential to maintain a healthy microbiota through an adequate diet, so that communication between the intestine and the brain occurs via the vagus nerve, regulating emotions and behavior. The objective of this research is to clarify how nutrition influences the prevention and control of anxiety disorders, as well as how dietary nutrients play a role in the formation of neurotransmitters responsible for our emotional behavior. The methodology was based on the search for articles published between 2014 and 2024 in the Google Scholar, CAPES, SCIELO and PubMed databases. Diet can have positive effects on the regulation or prevention of mental disorders such as anxiety, by acting on the intestinal microbiota, favoring the synthesis of tryptophan.